2018
DOI: 10.2174/1385272822666180123150323
|View full text |Cite
|
Sign up to set email alerts
|

Review on Life Cycle of Parabens: Synthesis, Degradation, Characterization and Safety Analysis

Abstract: In this review, we show the life cycle of parabens, commonly used preservatives that exist in nature and commercial products. Typical synthetic methods to produce parabens, and a set of complimentary characterization techniques to monitor the composition of parabens are also highlighted. These includes solid state analysis using Scanning Electron Microscope (SEM), Differential Scanning Calorimetry (DSC) and X-Ray Diffraction (XRD), in-situ monitoring of crystallization process using Focused Beam Reflectance Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 134 publications
0
13
0
Order By: Relevance
“…As an alternative to burning the lignin waste stream, current efforts are therefore focused on “lignin-first” bio-refining principles, in which lignin is used for the production of high-value chemicals ( Schutyser et al, 2018 ; Yang et al, 2019 ; de Vries et al, 2021 ). An example of such a product is p HBA, which can be esterified with various alcohols to form parabens that are widely used as preservatives in the cosmetics and pharmaceutical industries ( Yang et al, 2018 ). In addition, carboxylation of p HBA can be used to make terephthalate, the key precursor in PET plastics ( Bai et al, 2016 ), which is currently produced from the petrochemical p -xylene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an alternative to burning the lignin waste stream, current efforts are therefore focused on “lignin-first” bio-refining principles, in which lignin is used for the production of high-value chemicals ( Schutyser et al, 2018 ; Yang et al, 2019 ; de Vries et al, 2021 ). An example of such a product is p HBA, which can be esterified with various alcohols to form parabens that are widely used as preservatives in the cosmetics and pharmaceutical industries ( Yang et al, 2018 ). In addition, carboxylation of p HBA can be used to make terephthalate, the key precursor in PET plastics ( Bai et al, 2016 ), which is currently produced from the petrochemical p -xylene.…”
Section: Discussionmentioning
confidence: 99%
“…These groups could theoretically be separated and used as high-value phenolic chemicals. For example, p -hydroxybenzoic acid ( p HBA, indicating the “free” form) can be esterified with various alcohols to produce parabens that are commonly used as preservatives in the pharmaceutical and cosmetics industries ( Yang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Tanaka et al found that oiling-out changed the composition of the mother phase that inhibited the incorporation of impurity into the crystal . In this work, propyl paraben, widely used as a preservative, was used with a solvent model system of water and ethanol for oiling-out/liquid–liquid phase separation crystallization. , …”
Section: Introductionmentioning
confidence: 97%
“…8 In this work, propyl paraben, widely used as a preservative, was used with a solvent model system of water and ethanol for oiling-out/liquid−liquid phase separation crystallization. 9,10 Particle agglomeration is common in oiling-out crystallization due to the bridging effect of oil droplets that agglomerated the particles. 11,12 The heavy agglomeration usually leads to large particle size and broad distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Parabens are resistant to biological degradation. Therefore, they have been quantified in a large number of water bodies like rivers and lakes and effluents from wastewater treatment plants worldwide [5][6][7]. In a recent work published by Honda et al [8] that was performed in 8 different countries, including Asian countries as well as Greece and the USA, the researchers detected propyl paraben (PP) in 80.3% of the urinary samples, with an average concentration of 1.21 µg/L.…”
Section: Introductionmentioning
confidence: 99%